Penerapan Asas Ultimum Remidium dalam Penegakan Hukum Pidana di Bidang Cukai - Indrawati Indrawati; Bendito Menezes (University of Merdeka Malang, 2018)
Strict efforts in enforcing excise laws, criminal sanctions are used as a tool to provide maximum forced power for the excise duty community. But the truth is that criminal provisions are the last resort when administrative sanctions no longer work optimally. This study uses normative legal research methods. An offense to be categorized as a criminal offense cannot be separated from the legality of the legal subject, namely the BKC businessman and the legal object, namely the BKC and the Excise Band. If one of the legal subjects or legal object is illegal, then the violation committed is a form of criminal offense. In addition, an act can be convicted under the Customs law if it meets the following criteria: explicitly and clearly formulated as a violation, significantly causing state losses, and is a recurring act, or state losses incurred cannot be repaired. The application of the principle of ultimum remidium in law enforcement in the excise sector needs to use the theory of restorative justice to restore state losses caused by criminal offenders in the excise field, and social cost theory to provide additional costs and risks for criminals to dissuade them commit crime.How to cite item: Indrawati, I., Menezes, B. (2018). Penerapan Asas Ultimum Remidium dalam Penegakan Hukum Pidana di Bidang Cukai. Jurnal Cakrawala Hukum, 9(1), 11-20. doi:https://doi.org/10.26905/idjch.v9i1.2118